The Moderating Role of Foreign Investment in the Relationship between Economic Growth Determinants in Sumatra Island - Aisar Riski Baizura; T Zulham; Vivi Silvia (Graha Primera Saintifika, 2026)
Economic growth in Sumatra Island still faces structural challenges, especially related to the high level of open unemployment, the quality of human development, and the effectiveness of local government spending. On the other hand, the role of foreign investment in strengthening the relationship between these factors and economic growth has not yet shown empirical consistency, so it is important to study it more deeply. This study aims to evaluate the effect of open unemployment rate, Human Development Index (HDI), and government expenditure on economic growth in Sumatra Island, by including foreign investment as a moderating variable. This study uses panel data from ten provinces for the period 2011-2024 and is analyzed using the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The results show that the open unemployment rate has a significant negative effect on economic growth, while the Human Development Index (HDI) has no statistical effect. Government spending has a significant negative effect, indicating that the effectiveness of regional spending is not yet optimal in driving economic growth. In the moderation test, foreign investment was proven to strengthen the effect of government spending on economic growth, but it was not able to significantly moderate the effect of unemployment and HDI. These findings confirm that foreign investment is more effective when accompanied by good fiscal governance and human resource readiness. This study recommends optimizing the quality of public spending, implementing productive job creation programs, and synergizing foreign investment with regional human resource capacity development to promote inclusive and sustainable economic growth.